2019
DOI: 10.1111/1742-6723.13303
|View full text |Cite
|
Sign up to set email alerts
|

Review article: Goals‐of‐care discussions for adult patients nearing end of life in emergency departments: A systematic review

Abstract: Goals-of-care discussions at end-oflife are associated with increased patient satisfaction and reduced treatment burdens, reduced family and healthcare worker distress and healthcare costs, while achieving equal life-expectancy. It is unclear how goals-of-care discussions should occur. The objective of the study was to determine which patients could benefit, requirements, content, documentation, and harms and benefits of emergency medicine goals-of-care discussions. We sought primary evidence on goals-of-care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 34 publications
3
21
0
Order By: Relevance
“…Despite a focus on people at EOL, most studies did not include an EOL definition, although EOL care is well defined in policies and guidelines . This finding aligns with a recent systematic review of goals of care discussion for adult patients nearing EOL in the ED which reported that there is no common understanding of the meaning, purposed or desired outcomes of these conversations in the ED and that the concept was also poorly defined . Authors recommended that a standardised definitions and outcome measures are needed in this area .…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Despite a focus on people at EOL, most studies did not include an EOL definition, although EOL care is well defined in policies and guidelines . This finding aligns with a recent systematic review of goals of care discussion for adult patients nearing EOL in the ED which reported that there is no common understanding of the meaning, purposed or desired outcomes of these conversations in the ED and that the concept was also poorly defined . Authors recommended that a standardised definitions and outcome measures are needed in this area .…”
Section: Discussionsupporting
confidence: 75%
“…This finding aligns with a recent systematic review of goals of care discussion for adult patients nearing EOL in the ED which reported that there is no common understanding of the meaning, purposed or desired outcomes of these conversations in the ED and that the concept was also poorly defined . Authors recommended that a standardised definitions and outcome measures are needed in this area . Furthermore, cultural factors potentially influencing EOL care delivery were not evident in the articles reviewed.…”
Section: Discussionsupporting
confidence: 64%
“…It is often used to cover discussions about treatment intent and planning end stage care with patients [27]. The term is often confused with Advance Care Planning (ACP) or discussions that relate to treatment limitation [28], so establishing a common understanding of what discussing 'goals of care' entails is important [22]. Goals of care conversations are usually driven by the patient's and family's hopes, fears, expectations, and preferences for information, with treatment and care plan decisions often based on discussion and consideration of patient comfort and quality of life [27].…”
Section: Patient-centred Carementioning
confidence: 99%
“…Based on prior research on the outcomes of IHT patients and the effects of GoC discussions we suspect that early delivery of prognostic information and GoC discussions may have prevented some of these transfers from occurring, thereby possibly improving patient and family satisfaction, reducing treatment burden, and reducing costs. [16][17][18][19][20][21] The majority of patients in this study came from ED settings. Barriers to GoC discussions occurring in ED settings likely include time limitations, provider comfort level with these discussions, lack of training in conducting GoC discussions, and availability of palliative care resources for potential care transitions.…”
Section: Resultsmentioning
confidence: 99%